The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1087054720925898
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Therapeutic Horseback Riding to the Improvement of Executive Functions and Self-Esteem Among Children With ADHD

Abstract: Background: Attention deficit hyperactive disorder (ADHD) is associated with difficulties in executive functions (EFs), ( assessed by questionnaires) and self-esteem. Objective: To examine the contribution of therapeutic horseback riding to the EFs’ improvement and self-esteem. Method: In total, 123 Israeli children diagnosed with ADHD participated in the study. The study group participated in 20 weeks of therapeutic horseback riding sessions in addition to receiving medication, whereas the control group recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…[8][9][10][11][12][13]31 Two recent studies also used the BRIEF and found statistically significant improvements, lending further support to the current findings. 14,15 The authors' medium effect sizes correspond with previous findings of similar magnitude. 4 If a nontherapeutic equine program can shift behavioral symptoms from a negative to a positive trajectory, as shown in this study, it may be advantageous as an intervention and early intervention for atrisk youth displaying behavioral difficulties such as those associated with ADHD.…”
Section: Effect On Behavior and Attentionsupporting
confidence: 87%
See 3 more Smart Citations
“…[8][9][10][11][12][13]31 Two recent studies also used the BRIEF and found statistically significant improvements, lending further support to the current findings. 14,15 The authors' medium effect sizes correspond with previous findings of similar magnitude. 4 If a nontherapeutic equine program can shift behavioral symptoms from a negative to a positive trajectory, as shown in this study, it may be advantageous as an intervention and early intervention for atrisk youth displaying behavioral difficulties such as those associated with ADHD.…”
Section: Effect On Behavior and Attentionsupporting
confidence: 87%
“…The current approach deviates from most methodologies [8][9][10][11][12][13][14][15][16] in the field by running an equine program without specific therapeutic content. It also uses quantitative measures, where past research into equine programs without therapist involvement have used qualitative approaches.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies focused on Mounted‐EAT participation for a broad range of mental health and behavioural issues across these populations. The issues included persons struggling with substance use (Collingwood et al, 2021; Gatti et al, 2020; Kern‐Godal et al, 2015; Kern‐Godal, Brenna, Arnevik, et al, 2016; Kern‐Godal, Brenna, Kogstad, et al, 2016); youth at‐risk (Bachi et al, 2012; Burgon, 2011); children with ADHD (Aviv et al, 2020; Cuypers et al, 2011; Hyun et al, 2016; Jang et al, 2015; Oh et al, 2018; So et al, 2017; Yoo et al, 2016); youth with self‐harming behaviours (Carlsson, 2017); persons with histories of trauma (Craig, 2020; Mueller & McCullough, 2017; Naste et al, 2018; Yorke et al, 2013); veterans with post‐traumatic stress disorder (PTSD; Johnson et al, 2018, 2021; Lanning et al, 2017); adults with schizophrenia (Cerino et al, 2011; Collingwood et al, 2021; Corring et al, 2013); women with eating disorders (Lutter & Smith‐Osborne, 2011; Sharpe, 2014); youth with severe emotional disorders (Roberts & Honzel, 2020); women who have had breast cancer treatment (Cerulli et al, 2014); and children with stressful home environments already receiving school counselling (Pendry, Carr, et al, 2014; Pendry, Smith, et al, 2014; Pendry & Roeter, 2013).…”
Section: Resultsmentioning
confidence: 99%